Respostas

2013-04-14T03:36:22-03:00

Considerando "quadro" = quadrado, temos:

 

\left \{ {{a+b= -8} \atop {2a^2-b=9}} \right.

 

somando a primeira e a segunda equação temos:

 

2a^2 + a = 1 \\ <=> 2a^2 + a - 1 = 0

 

 \Delta = 1^2 - 4 \cdot 2 \cdot (-1) \\ \Delta = 1 + 8 \\ \Delta = 9

 

a_1 = \frac {-1 +\sqrt9}{2\cdot 2} \ ou \ a_2 = \frac {-1 - \sqrt9} {2\cdot 2} \\ \\ \\ a_1 = \frac {1} {2} \ ou \ a_2=-1

 

para a = -1

-1 + b = -8

b = -7

 

ou

 

a = 1 / 2

1 / 2 + b = -8

b = -16-1 / 2

b = -17 / 2